Bioactive Surface Modification Of Ti-Nb Alloy By Alkaline Treatment In Potassium Hydroxide Solution - Basry, Nur Adila Amira (2020)
Alkaline treatment of biocompatible and non-toxic new  structure Ti alloy implant in potassium hydroxide for modifying bioactivity of the alloy was investigated. Ti-40wt%Nb was fabricated by powder metallurgy method by milling of Ti-Nb mixture, pressing at 550MPa and -sintering at 1200°C for 2 hours. Alkaline treatment of the alloy was studied in the potassium hydroxide (KOH) aqueous solution at 60°C for 24 hours at different concentration of (i.e., 0.5 and 5M). The effect of post heat was investigating by annealed alkaline treated alloy at 600°C for 2 hours. The responsive behavior of the alloy alkaline treated alloy was compared to pure Ti and Nb. X-ray diffraction analysis showed the presence of amorphous alkaline titanate hydrogel layer such as titanium hydrate, potassium hydrogen titanium oxide, and niobium oxide for 0.5M treatment. For 5M, new phases are noticed (potassium titanium oxide and dipotassium dititanium oxide). The FTIR analysis show two significant band of OH at 3223 cm-1 and 1633 cm-1 on the Ti-40wt%Nb surface after alkaline and post heat treatment. Morphology observation under scanning electron microscope and elemental analysis indicate the deposition of titanate layer with the presence of high composition of potassium and oxygen. Bioactivity study in Hanks solution for 1 day discovered the trace of Ca and P elements on alloy surfaces treated in different concentration after alkaline as well as annealing treatment. These findings suggest that the new -Ti alloy with 40wt% Nb were feasible for alkaline treatment in KOH solution forming potassium based titanate layer that were prerequisite for bone mineral apatite deposition.